Quantum field theory in condensed matter physics - Tsvelik, Alexei M. (Cambridge University Press, 2003)
This book is a course in modern quantum field theory for condensed matter physics. The book is intended for graduate students, postdoctoral associates and independent researchers working condensed matter physics.